2001
DOI: 10.1074/jbc.m108291200
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of HAb18G/CD147 in Regulation of Store-operated Calcium Entry and Metastasis of Human Hepatoma Cells

Abstract: The present study examined the effect of hepatomaassociated antigen HAb18G (homologous to CD147) expression on the NO/cGMP-regulated Ca 2؉ mobilization and metastatic process of human hepatoma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
113
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(115 citation statements)
references
References 44 publications
2
113
0
Order By: Relevance
“…These results suggest that HAb18G/ CD147 plays a role in HCC invasion via regulation of MMP production by both tumor cells and surrounding fibroblasts, thus influencing the balance of tumor microenvironment, and the modulation of that by fibroblasts was more critical in the process. Our previous study also showed that HAb18G/ CD147 was involved in tumor metastasis and invasion as a signal transduction molecule by regulating Ca 2+ inflow (25,27). All these findings show that HAb18G/CD147 may play some important roles in HCC progression, including adhesion, migration, and enzymes degradation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These results suggest that HAb18G/ CD147 plays a role in HCC invasion via regulation of MMP production by both tumor cells and surrounding fibroblasts, thus influencing the balance of tumor microenvironment, and the modulation of that by fibroblasts was more critical in the process. Our previous study also showed that HAb18G/ CD147 was involved in tumor metastasis and invasion as a signal transduction molecule by regulating Ca 2+ inflow (25,27). All these findings show that HAb18G/CD147 may play some important roles in HCC progression, including adhesion, migration, and enzymes degradation.…”
Section: Discussionmentioning
confidence: 92%
“…Our previous reports suggested that HAb18G/CD147 was an HCC-associated antigen and was possibly related to HCC invasion in vitro (25)(26)(27). In the present study, we examined the role of HAb18G/CD147 in HCC invasion and metastasis in vitro, and in an orthotopic model of HCC in nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, NO-releasing agents have been shown to suppress the metastatic tumor cell behavior in various in vitro and in vivo tumor models by decreasing angiogenesis and, therefore, tumor cell invasion. [9][10][11][12][13] The anti-invasiveness and anti-metastatic properties of NO have been attributed either to inhibition of angiogenic factors such as β-FGF and TGFβ1, [9][10][11] or induction of TIMP-2 production and inhibition of p38. 13 Alternatively, NO has been proposed to interfere with the storeoperated calcium mobilization through regulation of the NO/ cGMP-mediated mechanism, 10 or it can prevent the excessive formation of oxygen radicals and peroxynitrate (ONOO -), which cause cell damage and facilitate tumor metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are in agreement with other studies showing the inhibitory effects of NO-releasing agents in metastatic tumor cell behavior both in vitro and in vivo. [9][10][11][12][13] The challenge regarding NO donors as therapeutic agents is to deliver NO in a sustained and controlled manner. NO donors that spontaneously generate large amounts of NO, independent of iNOS induction, are activated at physiological pH.…”
Section: Discussionmentioning
confidence: 99%
“…HAb18G/CD147, which belongs to the CD147 family, is a transmembrane glycoprotein that was cloned by screening a human HCC cDNA library using a monoclonal HAb18 antibody in our laboratory (Jiang et al, 2001). The molecular weight of CD147 is variable, ranging between 35 and 65/kDa depending on the degree of glycosylation.…”
Section: Introductionmentioning
confidence: 99%